The Effect of Financial Performance on Stock Prices with Macroeconomic Factors as Control Variables - Nurhusna, Nabilah; Zulpahmi; Al Azizah, Ummu Salma; Legowati, Diah Ayu (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This study aims to analyze the effect of financial performance on stock prices, with inflation and foreign exchange rates as controlling variables. Financial performance is approximated by four ratios, which are Net Profit Margin (NPM), Return on Assets (ROA), Debt to Equity Ratio (DER), and Earnings per Share (EPS). A total of 70 observations were analysed using a quantitative approach through panel data regression. The analysis showed that ROA and DER can affect stock prices. Conversely, NPM and EPS cannot influence stock prices. On the other hand, macroeconomic factors as control variables influence stock prices simultaneously but cannot influence them partially. These findings are expected to be taken into consideration by investors when formulating their investment strategies.